Genome-wide identification, characterization, and genetic diversity of CCR gene family in Dalbergia odorifera - Wang, Yue; Xu, Jieru; Zhao, Wenxiu; Li, Jia; Chen, Jinhui (Frontiers in Plant Science, 2022)
Lignin is a complex aromatic polymer plays major biological roles in maintaining the structure of plants and in defending them against biotic and abiotic stresses. Cinnamoyl-CoA reductase (CCR) is the first enzyme in the lignin-specific biosynthetic pathway, catalyzing the conversion of hydroxycinnamoyl-CoA into hydroxy cinnamaldehyde. Dalbergia odorifera T. Chen is a rare rosewood species for furniture, crafts and medicine. However, the CCR family genes in D. odorifera have not been identified, and their function in lignin biosynthesis remain uncertain. Here, a total of 24 genes, with their complete domains were identified. Detailed sequence characterization and multiple sequence alignment revealed that the DoCCR protein sequences were relatively conserved. They were divided into three subfamilies and were unevenly distributed on 10 chromosomes. Phylogenetic analysis showed that seven DoCCRs were grouped together with functionally characterized CCRs of dicotyledons involved in developmental lignification. Synteny analysis showed that segmental and tandem duplications were crucial in the expansion of CCR family in D. odorifera, and purifying selection emerged as the main force driving these genes evolution. Cis-acting elements in the putative promoter regions of DoCCRs were mainly associated with stress, light, hormones, and growth/development. Further, analysis of expression profiles from the RNA-seq data showed distinct expression patterns of DoCCRs among different tissues and organs, as well as in response to stem wounding. Additionally, 74 simple sequence repeats (SSRs) were identified within 19 DoCCRs, located in the intron or untranslated regions (UTR), and mononucleotide predominated. A pair of primers with high polymorphism and good interspecific generality was successfully developed from these SSRs, and 7 alleles were amplified in 105 wild D. odorifera trees from 17 areas covering its whole native distribution. Overall, this study provides a basis for further functional dissection of CCR gene families, as well as breeding improvement for wood properties and stress resistance in D. odorifera.